An assessment of the impact of silviculture and forest management regimes to forest cover change in the Churia region during 1992 to 2014 - Pokharel, B. K.; Uprety, D. R.; Niraula, R. R.; Pokharel, P. R. (Banko Janakari, 2018)
A study was conducted in the Churia region in 2014 to assess the change in forest cover as an outcome of the performance of various forest management regimes and silvicultural practices with the main objective to find the gap between those two. Geographic Information System (GIS) and Remote Sensing (RS) were used to compare the satellite imageries for the period of 1992 to 2014 in order to analyse the state of forest cover change. The demarcation of community forest boundaries was conducted based on available boundary maps and transferred to Google earth and GIS platform. Results showed that overall forest cover in the Churia region was increased by 7500 ha (1%) in 22 years, i.e. 1.35 million ha (76%) in 1992 to 1.36 million ha (77%) in 2014. The rate of deforestation in the Churia region was reduced as compared to the national average. However, degradation of landscape was visible at riverbeds and cultivation lands close to the riverbeds. It was also found that the area of dense forest was increased by 42,000 ha, whereas the area covered by bushes and grassland was reduced by 39,000 ha. The study further showed that there was a decline in cultivated land by 20,000 ha. Comparing the forest cover change in community forests with that of other management regimes, silvicultural practices in community forest areas have brought relatively better positive changes in the forest condition. It may be due to periodic silviculture operations carried out collectively by local communities. In the assessment, however, various elements of tenure rights and responsibilities of community, government and private forest and tree owners were identified and key silvicultural practices adopted by these regimes were highlighted as the drivers of positive or negative outcomes of forest cover change. Banko Janakari A Journal of Forestry Information for Nepal Special Issue No. 4, 2018, Page : 36-44